2023
DOI: 10.3389/fpls.2023.1124750
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of carotenoid and flavonoid biosynthetic pathways in Lactuca sativa var capitate L. in protected cultivation

Abstract: In the face of a growing world population and limited land, there is an urgent demand for higher productivity of food crops, and cultivation systems must be adapted to future needs. Sustainable crop production should aim for not only high yields, but also high nutritional values. In particular, the consumption of bioactive compounds such as carotenoids and flavonoids is associated with a reduced incidence of non-transmissible diseases. Modulating environmental conditions by improving cultivation systems can le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 76 publications
1
16
3
Order By: Relevance
“…Larissa, an effect of the treatments was observed for β-carotene. This is in contrast to Caldwell and Britz (2006) and Harbart et al (2023), who found increased β-carotene, lutein, and neoxanthin concentrations after a supplemental UVA and UVB treatment of 16 lettuce cultivars, and under polytunnel treatment.…”
Section: Carotenoidscontrasting
confidence: 95%
See 4 more Smart Citations
“…Larissa, an effect of the treatments was observed for β-carotene. This is in contrast to Caldwell and Britz (2006) and Harbart et al (2023), who found increased β-carotene, lutein, and neoxanthin concentrations after a supplemental UVA and UVB treatment of 16 lettuce cultivars, and under polytunnel treatment.…”
Section: Carotenoidscontrasting
confidence: 95%
“…In a previous study, different shading intensities (based on the cardinal directions) had little to no effect on carotenoids in kale (Bayer et al, 2022). It is noteworthy that Harbart et al (2023) reported no differences between foil treatments and their control on a transcriptional level (phytoene synthase), suggesting a posttranscriptional regulated effect that increased carotenoid concentrations but was not observed in our study. However, such post-transcriptional regulation might explain the diverse results reported in the literature.…”
Section: Carotenoidscontrasting
confidence: 83%
See 3 more Smart Citations